Local information services in Medellin : technology, institutions, communities and power (2017)
RESUMEN: This article examines the politics of technology and information by exploring a case study of local information service provision in Medellin, Colombia. Local Information Service (LIS) is defined as a community centre where information deemed relevant to local communities is generated, stored, organized and disseminated through print and digital means. Using a social construction of technology approach, the article attempts to deconstruct the implementation and delivery of LIS in Medellin, Colombia and analyse how empowering and disempowering discourses form through relationships between institutions and citizens laden with social and economic inequality. The article analyses the development and deployment of this artefact and positions LIS as a socio-technical system, embedded with political, social, cultural, and economic values. We describe the unintended consequences of this deployment through a multilevel perspective of the head organisation and the smaller 195 local institutions that support it. The article challenges and operationalises the social construction of ‘local’ in local information by highlighting practices of social exclusion and resistance embedded within the design of the service. This case provides a vantage point from which to examine how relevant social groups interpret and engage with technological devices and the implications of this for the communities the device is intended to serve.